Peran Leverage dalam Memediasi Hubungan Current Ratio dan Inflasi Terhadap Kinerja Keuangan pada Perusahaan Manufaktur Non-Cyclical yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024 - Lia Nur Hidayati; Diana Puspitasari; Rudi Kurniawan; Amalia Nur Chasanah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This research looks at how Indonesian non-cyclical manufacturing businesses  financial operations are affected by inflation and liquidity, using leverage as a mediating variable. The study sample consists of 77 companies listed on the Indonesian Stock Exchange for the years 2021–2024. Secondary data is analyzed using the PLS-SEM method. This study focuses on the relationship between inflation and financial performance through the use of leverage. The research findings indicate that liquidity (Current Ratio) has a negative and significant impact on financial performance, whereas inflation and leverage do not. Additionally, leverage does not address the relationship between inflation and liquidity with regard to financial performance. This indicates that excessive liquidity might reduce business efficiency. In order to obtain more comprehensive results, subsequent research is advised to increase sample size and incorporate more variables.